Chapter 11 Heat Pumps - Gerring, Dorothy (Taylor & Francis, 2024)
The funder would like the two following paragraphs to be included in the open access chapter: "This open access chapter was developed with support from Pacific Northwest National Laboratory with funding from the U.S. Department of Energy's Building Technologies Office to include advanced heat pump technologies that are critical to providing heating in buildings powered by renewable energy. This chapter was prepared in part as work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, nor any of their contractors, subcontractors or their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or any third party's use or the results of such use of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, process, or service by trade name, trademark, manufacturer, or otherwise, does not necessarily constitute or imply its endorsement, recommendation, or favoring by the United States Government or any agency thereof or its contractors or subcontractors. The views and opinions of authors expressed herein do not necessarily state or reflect those of the United States Government or any agency thereof, its contractors or subcontractors."" The author also wondered if the disclaimer published at the front of their book (below) should also be included, since this is apart from the book: ""The author and publisher of this book have put forth their best effort to ensure that the content contained herein is accurate and up-to-date. The purpose of this content is to assist the reader to understand the scope of work and the issues that need to be addressed when designing a building with a renewable energy system. Professional aid should be obtained when designing the specifics of any renewable energy system. The author and publisher shall not be held liable for incidental or consequential damages connected to, or arising from, the use of this book's content."